Exploring The Potential of Traditional Beverages as Welcome Drinks in The Hospitality Industry: A Case Study of GRAMM Hotel By Ambarrukmo Yogyakarta - Annamaria Kristinta Setyaningtyas; Lise Asnur; Ngatimin (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
This study aims to analyze the potential of traditional beverages as welcome drinks in the hospitality industry. The study employed a qualitative method using a case study approach at GRAMM Hotel by Ambarrukmo in Yogyakarta. Data were collected through interviews with the Front Office Department, the Food and Beverage Service Department, and hotel management, and were supplemented by observations and documentation. The results indicate that traditional beverages have high potential as welcome drinks because they represent local culture and provide a unique experience for guests. The beverages deemed most promising are secang jahe, jahe asem jawi, and lemongrass. These three beverages are served on a rotating basis according to the operational schedule and availability of raw materials to maintain product quality and provide variety for guests. Although there are challenges related to shelf life and the consistency of raw materials, the implementation of traditional beverages can increase the added value of services and strengthen the hotel’s image based on local culture.